In-person prospective audit and feedback on an oncology ward: development of an immunocompromised antimicrobial stewardship program - Hannah Imlay; Sage B. Greenlee; Brandon J. Tritle; Nora F. Fino; Emily S. Spivak (Cambridge University Press, 2024)
Abstract Objective: To describe clinical syndromes, opportunities for antimicrobial optimization, and acceptance of recommendations made by an immunocompromised antimicrobial stewardship program performing in-person prospective audit and feedback (IPPAF) on inpatient oncology services. Design: Retrospective cohort study. Setting: Three inpatient oncology services including patients with solid tumor malignancies in an academic cancer center. Patients: Hospitalized adults with oncologic malignancies receive antimicrobials for any indication. Methods: We reviewed all patients receiving antimicrobials on inpatient oncology services who were included in IPPAF and prospectively documented clinical syndromes represented, most common recommendations, and acceptance rate. We also examined the standardized antimicrobial administration ratio (SAAR) for oncology units over the study period. Results: Over 34 weeks, we performed 154 interventions for 138 patients. Metastatic malignancy was common (52%) and 90-day mortality was high (43%). Diagnostic uncertainty was common (33/154, 21%), as were cases of intra-abdominal pathology (30/154, 19%), pneumonia (25/154, 16%), and urinary tract infection (12/154, 8%). The most common recommendations were changes in duration (63/154, 41%) and stopping antimicrobials for syndromes determined to be noninfectious (29/154, 19%). Acceptance of interventions was high (77% overall) and several SAARs on the primary oncology unit significantly decreased after starting IPPAF. Conclusions: We identified numerous opportunities for antimicrobial optimization among solid tumor malignancy patients. Most clinical syndromes were ones also encountered frequently in non-oncology populations, but several were unique and represented opportunities for targeted education.